After the ivory tower falls: how college broke the American dream and blew up our politics-- and how to fix it (HarperCollins, HarperAudio, William Morrow an imprint of HarperCollins Publishers, 2022)
From Pulitzer Prize-winning journalist Will Bunch, the epic untold story of college--the great political and cultural fault line of American life Winner of the Athenaeum of Philadelphia Literary Award ^ Longlisted for the PEN/John Kenneth Galbraith Award for Nonfiction ^ "This book is simply terrific." --Heather Cox Richardson ^ "Ambitious and engrossing." --New York Times Book Review ^ "A must-read." --Nancy MacLean, author of Democracy in Chains Today there are two Americas, separate and unequal, one educated and one not. And these two tribes--the resentful "non-college" crowd and their diploma-bearing yet increasingly disillusioned adversaries--seem on the brink of a civil war. The strongest determinant of whether a voter was likely to support Donald Trump in 2016 was whether or not they attended college, and the degree of loathing they reported feeling toward the so-called "knowledge economy" of clustered, educated elites. Somewhere in the winding last half-century of the United States, the quest for a college diploma devolved from being proof of America's commitment to learning, science, and social mobility into a kind of Hunger Games contest to the death. That quest has infuriated both the millions who got shut out and millions who got into deep debt to stay afloat. In After the Ivory Tower Falls, award-winning journalist Will Bunch embarks on a deeply reported journey to the heart of the American Dream. That journey begins in Gambier, Ohio, home to affluent, liberal Kenyon College, a tiny speck of Democratic blue amidst the vast red swath of white, post-industrial, rural midwestern America. To understand "the college question," there is no better entry point than Gambier, where a world-class institution caters to elite students amidst a sea of economic despair. From there, Bunch traces the history of college in the U.S., from the landmark GI Bill through the culture wars of the 60's and 70's, which found their start on college campuses. We see how resentment of college-educated elites morphed into a rejection of knowledge itself--and how the explosion in student loan debt fueled major social movements like Occupy Wall Street. Bunch then takes a question we need to ask all over again--what, and who, is college even for--and pushes it into the 21st century by proposing a new model that works for all Americans. The sum total is a stunning work of journalism, one that lays bare the root of our political, cultural, and economic division--and charts a path forward for America.
Introduction: College like my grandma used to make , Life during wartime in Knox County, Ohio , When college in America almost became a public good , Why the Kent State massacre raised your tuition , Yuppies, dittoheads, and a "big sort" : college and the culture wars , The "whole college thing" awkwardly enters the 2020s , Gap year. The Quad: The four people you meet in today's America , A college debt crisis, Occupy Wall Street, and the rise of a new new left , From resentment of college to America's rejection of knowledge , The soul of a new Truman Commission , A bloodles war to save America's youth.

After the Ivory Tower Falls: How College Broke the American Dream and Divided the Nation, and How to Fix It (William Morrow, 2022)
From Pulitzer Prize-winning journalist Will Bunch, the epic untold story of college--the great political and cultural fault line of American life Winner of the Athenaeum of Philadelphia Literary Award ^ Longlisted for the PEN/John Kenneth Galbraith Award for Nonfiction ^ "This book is simply terrific." --Heather Cox Richardson ^ "Ambitious and engrossing." --New York Times Book Review ^ "A must-read." --Nancy MacLean, author of Democracy in Chains Today there are two Americas, separate and unequal, one educated and one not. And these two tribes--the resentful "non-college" crowd and their diploma-bearing yet increasingly disillusioned adversaries--seem on the brink of a civil war. The strongest determinant of whether a voter was likely to support Donald Trump in 2016 was whether or not they attended college, and the degree of loathing they reported feeling toward the so-called "knowledge economy" of clustered, educated elites. Somewhere in the winding last half-century of the United States, the quest for a college diploma devolved from being proof of America's commitment to learning, science, and social mobility into a kind of Hunger Games contest to the death. That quest has infuriated both the millions who got shut out and millions who got into deep debt to stay afloat. In After the Ivory Tower Falls, award-winning journalist Will Bunch embarks on a deeply reported journey to the heart of the American Dream. That journey begins in Gambier, Ohio, home to affluent, liberal Kenyon College, a tiny speck of Democratic blue amidst the vast red swath of white, post-industrial, rural midwestern America. To understand "the college question," there is no better entry point than Gambier, where a world-class institution caters to elite students amidst a sea of economic despair. From there, Bunch traces the history of college in the U.S., from the landmark GI Bill through the culture wars of the 60's and 70's, which found their start on college campuses. We see how resentment of college-educated elites morphed into a rejection of knowledge itself--and how the explosion in student loan debt fueled major social movements like Occupy Wall Street. Bunch then takes a question we need to ask all over again--what, and who, is college even for--and pushes it into the 21st century by proposing a new model that works for all Americans. The sum total is a stunning work of journalism, one that lays bare the root of our political, cultural, and economic division--and charts a path forward for America.

After the ivory tower falls (Harper Collins Publishers, 2022)
From Pulitzer Prize-winning journalist Will Bunch, a deeply reported look at the broken state of college in America, arguing that access to college is the defining political issue of our time, propelling everything from Occupy Wall Street to the election of Donald Trump to the George Floyd protests.

Summary of Will Bunch's After the Ivory Tower Falls (IRB, 2022)
Please note: This is a companion version & not the original book. Book Preview: #1 Kenyon College is a small, liberal arts school in Ohio. It was given a $75 million donation in 2017 to build a new West Quad, which included a new admissions office. The school is known for its rich and diverse student body, but one of its neighbors is the last remaining source of good blue-collar jobs in the area. #2 The students at Kenyon College, a small liberal arts school in Ohio, voted overwhelmingly for Joe Biden in the 2020 election. In the rest of the county, Trump won by 5 points.